Malignant Melanoma of the Vagina - A Case Report - Sultana, Nilufa; Ali, Chowdhury Md; Khanam, Rawshan Ara; Khatan, Prof Mahmuda (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 52 yrs old post menopausal lady was admitted in-the Gynae department of SSMC & Mitford Hospital with a small mass in the lower vagina, foul smelling discharge and occasional itching at that site for 1 year. Examination revealed a small, irregular, firm, partially necrosed, non tender growth with foul smelling brownish discharge 2cm below the external urethral meatus, uterus atrophied, cervix flashed, fornicesfree but few small, black, flat nodules scattered in the posterior vaginal wall. She had no history of exposure to any radiation or sunlight to that area or surgery but only received antitubercular drugs for six month for pulmonary tuberculosis. After conservative treatment excision biopsy was taken and histopathology revealed Malignant Melanoma. She was referred to cancer Institute for adjuvent radiotherapy. DOI: 10.3329/jbcps.v26i2.4190 J Bangladesh Coll Phys Surg 2008; 26:103-105